A feasibility study on "Momsie" a complementary baby food - Baita, Lorie Mae; Mirando, Dwight Vijie; Portea, Marion Jasper (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
The study aims to assess the feasibility of Momsie, a ready-to-eat complementary baby food. It was formulated to assist in providing an affordable energy-and-nutrient dense ready-to-eat complementary baby food for children below 3 years, especially those with cases of moderate-to-severe malnutrition. It is made up of local ingredients such as mongo, cacao and soy beans. For the first stage of the study, the key features of the product are established. From this, the product's main and indirect competitors were determined. Product strengths were used to further build up the product's advantage compared to its competitors. This led to the identification of the potential customers and market shares. Several marketing and sales strategies were also planned to attract these potential customers, which includes giving the potential customers a sample of Momsie. Currently, it is being marketed to entrepreneurs producing complementary foods. The product would be available in 25-gram serving packs distributed among supermarkets and sari-sari stores across Metro Manila at a suggested retail price of seven pesos (PhP 7.00) per piece. Momsie's primary market would target mothers aged 25-34 years that belong to CDE families, where malnutrition among young children are mostly prevalent. For the initial year, a marketing budget of Php 48,250.00 was identified. Furthermore, approximately, Php 1.376 million in revenues is expected for the first year. It is expected that this will increase up to Php 7.074 million for the succeeding years due to the increase in efficiency of the design capacity. For the next stage, projected demand for the product was used to determine the required amount of Momsie to be produced. As such.the minimum operating requirements were set up. This includes the identification and of the required number of machines and equipment to be used and the elimination of possible sites for the plant site. To minimize operating expenses, Momsie will rent a space measuring approximately 95.16 square-meter production plant at Sta. Maria, Bulacan, where it is both near the suppliers of its raw materials (mung, cacao, soybeans and peanuts) which is Central Luzon and at the same time it is easily accessible to its customers in Metro Manila. The organization was also determined to be partnership and key people for the start-up of the organization were also assigned. The next stage showed that a one year working capital of Php 1,187,869.10 is needed and the total project cost of l,741,831.41 for the first year was computed. After identifying the necessary project costs to set up the business, it was planned how to source the required funds. It was determined that seventy percent (70%) of the total project cost will be financed by loan from BPI and the remaining thirty percent (30%) will be from equity. Financial statements were then prepared to determine the feasibility of operating the business, and analyses made from these financial statements showed that the business is indeed profitable. After the financial study, it is determined that the operation is financially feasible. The benefits of Momsie, aside from its contribution to government revenue, include the utilization of our local ingredients as recipe of our product and providing additional earnings to our citizen. Based from this, the project was also deemed socially beneficial venture. Overall, this project is feasible in all aspects.
Submitted in partial fulfillment of the course requirements in IE 153 : Project development and management.
Keywords: Baby foods industry -- Philippines; Feasibility studies